Mental health index of the elderly population in Medellín (Colombia)−2021: a factorial analysis - Ochoa-Nieto, Sandra Patricia; Benjumea-Gómez, Luisa María; Cardona-Arango, Doris; Segura-Cardona, Ángela; Segura-Cardona, Alejandra; Robledo-Marín, Carlos (Frontiers in Psychology, 2024)
Introduction: For people over 60 years of age, there are several risk factors for developing mental disorders. There are multiple domains of mental health, also considered as capacities, which can comprise the psychological well-being of older people. For this reason, it is considered that resilient coping, self-compassion, self-esteem, hopelessness, quality of life, and depression are the characteristics and adaptive mechanisms that bring together the main risk and protective factors for imbalance in mental well-being. Objective: Establish the demographic, social, and family factors, as well as the clinical characteristics and lifestyle habits that influence the mental health of the elderly in the city of Medellín, in the year 2021, to build a mental health index. Methodology: Study with a quantitative approach, retrospective temporality, and secondary source. A crosssectional survey was carried out with the SABAM Project (Health and Mental Well-being of the elderly person from five cities in Colombia in 2021 by its Spanish acronym) database (secondary source), part of the